Scribes Writing Scripture : Doublets, Textual Divination, and the Formation of the Book of Jeremiah - Ghormley, Justus Theodore, (Vetus Testamentum, Supplements ;, 2022)
The biblical book of Jeremiah was frequently expanded and revised through duplication by anonymous scribes in ancient Judea. Who were these scribes? What gave them the authority to revise divinatory texts like Jeremiah? And when creating duplicates, what did they think they were doing? In Scribes Writing Scripture: Doublets, Textual Divination, and the Formation of Jeremiah , Justus Theodore Ghormley explores possible answers to these questions. The scribes who revised Jeremiah are textual diviners akin to divining scribal scholars of ancient Near Eastern royal courts; and their practice of expanding Jeremiah through duplication involves techniques of textual divination comparable the practice of textual divination utilized in the formation of ancient Near Eastern divinatory texts.